Exploring the contemporary spatial and temporary dynamics of the settlement hierarchy and system in Serbia's Srem Region - Đerčan Bojan; Bjelajac Dajana; Bubalo-Živković Milka; Lukić Tamara; Gatarić Dragica; Pogrmić Zorica (Geographica Pannonica)
Newer trends of balanced regional development emphasize the development of functional integrational areas and strong spatial and functional relations based on the nodal concept and a functional process approach. Therefore, it is essential to determine the hierarchy of settlements in the network, which defines their demographic and functional capacity. This paper identifies the nature and characteristics of urban primacy in the Srem region in Serbia, using the rank-size rule and urban primacy index, as well as the hierarchy of settlements in the network, by calculating the importance of secondary activities and the centralization of the settlements. The results confirmed that while urban primacy is not expressed, the hierarchy of the settlements remains dominated by urban and suburban centres.